2017
DOI: 10.1016/j.pharmthera.2017.02.005
|View full text |Cite
|
Sign up to set email alerts
|

Tumor regulation of the tissue environment in the liver

Abstract: The tumor microenvironment (TME) in the liver plays an important role in primary and metastatic liver tumor formation and tumor growth promotion. Cellular and non-cellular components of the TME significantly influence tumor development, growth, metastatic spread, anti-tumor immunity and response to tumor therapy. The cellular components of the TME in the liver not only consist of infiltrating immune cells, but also of liver-resident cells such as liver sinusoidal endothelial cells (LSEC) and hepatic stellate c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
60
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 75 publications
(65 citation statements)
references
References 134 publications
(169 reference statements)
1
60
0
1
Order By: Relevance
“…Furthermore, the patients tolerated the treatment well. Numerous analyses in recent years have shown that tumor immune responses influence cancer formation and progression in advanced hepatic cancer [32], indicating the possible effectiveness of immune-based therapy as a cancer treatment option.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the patients tolerated the treatment well. Numerous analyses in recent years have shown that tumor immune responses influence cancer formation and progression in advanced hepatic cancer [32], indicating the possible effectiveness of immune-based therapy as a cancer treatment option.…”
Section: Discussionmentioning
confidence: 99%
“…Premalignant hepatocytes secrete cytokines, which attract macrophages to clear affected cells. However, if a tumor-preventive senescence program is bypassed, senescence-recruited myeloid cells promote HCC development [17,18]. Furthermore, APCs change their profile by secreting less immune-stimulatory antitumorigenic cytokines like interleukin-12 (IL-12) or IFN-Îł [19].…”
Section: Immunotherapeutic Preclinical and Translational Approaches Tmentioning
confidence: 99%
“…LSEC are also well known to participate in liver immune response by secreting cytokines upon pathogenic stimuli [8]. These cells also play a key role upon danger signal leading to fibrosis since, upon shear stress, they will undergo cytoskeletal remodeling, leading to a loss of fenestration [8,9]. Hepatic stellate cell (HSC), the liver fibroblasts, and producers of extracellular matrix are localized in the space of Disse, an area between hepatocytes and sinusoids, and thus are not directly exposed to the bloodstream.…”
Section: Introductionmentioning
confidence: 99%
“…These cells normally represent 5-8% of the total number of the liver cells. However, upon chronic inflammation, HSC undergo transformation to become myofibroblasts, the activated state of HSC [9][10][11]. Once activated, these cells proliferate and start secreting numerous components of the extracellular matrix creating a scarlike tissue [12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation